Polylysine supported salicylaldehyde schiff base molybdenum complex recyclable catalyst, preparation method and application thereof

CN122999282APending Publication Date: 2026-10-30LUDONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611165522.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而现有负载型金属催化剂存在金属活性组分在长期反应过程中易发生迁移、团聚,导致催化剂逐步失活,无法满足工业长期连续生产的要求;该类催化剂在低负载量下可实现金属活性组分高分散,一旦提高金属负载量,极易出现颗粒团聚、金属活性组分分布不均的现象,造成活性位点利用率显著下降,以至于负载量与分散性难以兼顾

Benefits of technology

本发明给出的多聚赖氨酸负载水杨醛希夫碱钼配合物催化剂是以多聚赖氨酸盐酸盐与碱的反应产物生物基的多聚赖氨酸(ε-PL)为负载载体,且多聚赖氨酸表面富含大量氨基和羟基等官能团,将其与水杨醛进行缩合反应得到水杨醛希夫碱配体,从而使得多聚赖氨酸与水杨醛希夫碱配体形成牢固的配位结合,在催化剂中钼源为活性中心,通过配位作用将水杨醛希夫碱钼配合物锚定在多聚赖氨酸载体表面,形成载体-配体-活性中心的稳定结构,提高了催化剂的负载量,由于多聚赖氨酸在水中或溶剂中能均匀分散且不易团聚,且设计是把催化活性中心钼逐个牢固锚定分散在聚合物链上,没有迁移和团聚的机会,抑制活性组分在高温或长期反应条件下的迁移、团聚和烧结,同时理论上一个氨基酸单元一个钼,负载量很高,有大量催化位点,催化效率高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999282A_ABST
    Figure CN122999282A_ABST
Patent Text Reader

Abstract

The present application belongs to the field of green catalysis technology, and relates to a recyclable catalyst of polylysine supported salicylaldehyde Schiff base molybdenum complex, a preparation method and application. Bio-based polylysine is used as a support carrier to break through the limitation of the environmental friendliness of traditional support carriers, combine the biocompatibility and rich functional groups of polylysine with the catalytic performance of salicylaldehyde Schiff base molybdenum complex and the low-cost advantage of molybdenum elements, realize the recyclable use of the catalyst, and form a three-in-one catalytic system of green carrier-high-efficiency active center-recyclable. The catalyst not only solves the recycling problem of the existing Schiff base molybdenum complex catalyst, but also reduces the catalytic cost, improves the greenness and economy of the catalytic process, and has simple preparation process and convenient large-scale production. The catalyst can promote the application and popularization of green catalysis technology in related industries, and has academic value, industrial value and environmental value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of green catalysis technology, and specifically relates to a recyclable catalyst, preparation method and application of polylysine-supported salicylaldehyde Schiff base molybdenum complex. Background Technology

[0002] 2-Amino-3-cyanobenzopyran compounds are a class of nitrogen-containing fused heterocyclic structures with high application value. They are widely found in natural products and drug molecules and possess biological activities such as antibacterial, antitumor, anti-inflammatory, and antioxidant properties. They are widely used in the synthesis of pharmaceutical intermediates and fine chemicals, and related catalytic synthesis technologies have always been a research hotspot in this field.

[0003] Currently, catalytic systems used for synthesizing these compounds are mainly classified into four categories: small organic molecule catalysts, solid acid catalysts, homogeneous metal Schiff base complexes, and supported metal catalysts. Among them, supported metal catalysts have been widely studied due to their ease of separation. Researchers can achieve effective dispersion of active components from nanoparticles to single atoms at low loading levels by controlling the support structure, surface functional groups, and metal-support interactions. Porous carbon, metal oxides, molecular sieves, metal-organic frameworks (MOFs), and common polymer materials are the mainstream supports. By constructing hierarchical pores, introducing structural defects, and modifying interfaces, the specific surface area and structural stability of the catalyst can be improved. However, existing supported metal catalysts are prone to migration and aggregation of the metal active components during long-term reactions, leading to gradual deactivation of the catalyst and failing to meet the requirements of long-term continuous industrial production. While these catalysts can achieve high dispersion of the metal active components at low loading levels, once the metal loading is increased, particle aggregation and uneven distribution of the metal active components easily occur, resulting in a significant decrease in the utilization rate of active sites, making it difficult to achieve both high loading and good dispersion. Summary of the Invention

[0004] To address the shortcomings of the prior art, the present invention aims to provide a recyclable catalyst, preparation method, and application of a polylysine-supported salicylaldehyde Schiff base molybdenum complex. The active components of this catalyst are less prone to migration, agglomeration, and sintering under high temperature or long-term reaction conditions, thus maintaining the catalyst's reactivity and stability during long-term industrial operation. Simultaneously, this catalyst can achieve high loading while maintaining high dispersion of the active components, ensuring uniform distribution of catalyst particle size and active components, and improving the utilization rate of effective active sites.

[0005] To solve the above-mentioned technical problems, the present invention provides a polylysine (PL) supported salicylaldehyde Schiff base molybdenum complex catalyst. The catalyst is prepared by adding a molybdenum source ethanol solution dropwise into an ethanol dispersion of salicylaldehyde Schiff base ligand, stirring and heating to react, filtering to obtain a salicylaldehyde Schiff base molybdenum complex (PL-SB-Mo) supported on the side chain of polylysine, and then removing impurities by Soxhlet extraction with ethanol. The salicylaldehyde Schiff base ligand (PL-SB) is prepared by dissolving polylysine hydrochloride in an alkaline solution, adding salicylaldehyde dropwise while stirring and heating to achieve Schiff base condensation, followed by cooling, filtration and washing at room temperature, Soxhlet extraction with ethanol, and vacuum drying.

[0006] The polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst of this invention uses bio-based polylysine (ε-PL), the reaction product of polylysine hydrochloride and base, as the supporting carrier. The surface of polylysine is rich in a large number of functional groups such as amino and hydroxyl groups. It undergoes a condensation reaction with salicylaldehyde to obtain salicylaldehyde Schiff base ligand, thereby forming a strong coordination bond between polylysine and salicylaldehyde Schiff base ligand. In the catalyst, the molybdenum source is the active center. Through coordination, the salicylaldehyde Schiff base molybdenum complex is anchored on the surface of the polylysine support, forming a stable structure of support-ligand-active center, which improves the catalyst loading. Since polylysine can be uniformly dispersed in water or solvent and is not easy to agglomerate, and the rigidity of the polylysine molecular chain itself makes molybdenum not easy to agglomerate, the covalent connection structure makes the coordination structure not easy to be destroyed and translocated, inhibiting the migration, agglomeration and sintering of active components under high temperature or long-term reaction conditions.

[0007] Salicylic aldehyde Schiff base ligands can significantly improve catalytic selectivity and activity by precisely modulating the electronic structure and redox properties of the molybdenum center through N and O atoms. Molybdenum, as the active component, replaces precious metal catalysts, significantly reducing catalyst costs. Furthermore, polylysine is a natural, biodegradable biopolymer with excellent hydrophilicity and biocompatibility. The entire process uses green solvents such as water and ethanol, and uncoordinated substances are removed through Soxhlet extraction, further enhancing the catalyst's environmental friendliness and long-term industrial stability. This fills the gap in using bio-based polylysine as a support for Schiff base molybdenum complexes, while also responding to the development needs of green catalysis and the circular economy.

[0008] In summary, the catalyst provided by this invention has the advantages of high loading capacity, high dispersibility, high utilization rate of active sites, resistance to sintering, inhibition of migration and agglomeration, and low cost and greenness.

[0009] Preferably, the alkaline solution is a potassium hydroxide solution, and the molar ratio of polylysine hydrochloride to potassium hydroxide in the potassium hydroxide aqueous solution is 1:1 to 10; the molar ratio of polylysine hydrochloride to salicylaldehyde is 1:1 to 10; and the molar concentration of the potassium hydroxide aqueous solution is 0.1 mol / L to 1 mol / L. Only when the molar ratio of polylysine hydrochloride to potassium hydroxide in the potassium hydroxide aqueous solution is 1:1 to 10 can more amino groups be released from polylysine hydrochloride. Only when the molar ratio of polylysine hydrochloride to salicylaldehyde is 1:1 to 10 can the released amino groups be ensured to react completely, thereby increasing the amount of salicylaldehyde Schiff base ligand formed.

[0010] Preferably, the molybdenum source is any one of molybdenum acetylacetonate, molybdenum dichlorodioxide, sodium molybdate, or ammonium molybdate. Preferably, the reaction temperature of the Schiff base condensation reaction is 20℃~80℃, the reaction time is 1h~12h, the molybdenum source is molybdenum acetylacetonate, and the reaction temperature of the salicylaldehyde Schiff base ligand ethanol dispersion with the ethanol solution containing molybdenum acetylacetonate is 25℃~80℃, and the reaction time is 2h~12h.

[0011] Preferably, the mass concentration of the salicylaldehyde Schiff base ligand ethanol dispersion is 50 g / L to 150 g / L.

[0012] Preferably, the mass ratio of the salicylaldehyde Schiff base ligand to molybdenum acetylacetonate is 1.5:5~20, and the mass concentration of the molybdenum acetylacetonate ethanol solution is 50g / L~200g / L.

[0013] This invention provides a method for preparing a polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst, comprising the following steps: Polylysine hydrochloride was dissolved in an alkaline solution, and salicylaldehyde was added dropwise with stirring. The reaction was carried out by heating and Schiff base condensation. After cooling, the reaction product was filtered and washed at room temperature, and unreacted salicylaldehyde was removed by Soxhlet extraction with ethanol. The extract was dried under vacuum to obtain salicylaldehyde Schiff base ligand (PL-SB). Salicylaldehyde Schiff base ligand was dispersed in ethanol to obtain a salicylaldehyde Schiff base ligand ethanol dispersion. An ethanol solution containing a molybdenum source (an ethanol solution of molybdenum acetylacetone) was added dropwise to the salicylaldehyde Schiff base ligand ethanol dispersion, and the reaction was carried out under stirring and heating. After the reaction, the mixture was filtered to obtain a salicylaldehyde Schiff base molybdenum complex (PL-SB-Mo) supported on the side chain of polylysine. The salicylaldehyde Schiff base molybdenum complex supported on the side chain of polylysine was subjected to Soxhlet extraction with ethanol to remove acetylacetone and unreacted molybdenum acetylacetone. The extract was dried under vacuum to obtain the polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst.

[0014] This invention discloses the application of a polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst in the synthesis of 2-amino-3-cyanobenzopyran compounds.

[0015] Preferably, the preparation method of the 2-amino-3-cyanobenzopyran compound is as follows: Using 63.9 mg of polylysine-supported Schiff base molybdenum complex as a catalyst, 10 mmol of naphthol, 10 mmol of aromatic aldehyde, and 10 mmol of malononitrile were reacted in a mixed solution of 2 mL of water and ethanol at 80 °C for 0.5 h to 2 h. The mixture was filtered while hot, washed with ethanol, and the filtrate was cooled to crystallize. The crystals were then filtered and washed to obtain 2-amino-3-cyanobenzopyran compounds, wherein the naphthol was α-naphthol or β-naphthol.

[0016] Preferably, the volume ratio of water to ethanol in the mixed solution of water and ethanol is 1~2:1.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: The polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst of this invention uses bio-based polylysine (ε-PL), the reaction product of polylysine hydrochloride and base, as the supporting carrier. The surface of polylysine is rich in numerous amino and hydroxyl functional groups. This is achieved by condensing polylysine with salicylaldehyde to obtain salicylaldehyde Schiff base ligands, thus forming a strong coordination bond between polylysine and the salicylaldehyde Schiff base ligands. In the catalyst, the molybdenum source serves as the active center. Through coordination, the salicylaldehyde Schiff base molybdenum complex is anchored to the surface of the polylysine support, forming a stable carrier-ligand-active center structure, which increases the catalyst loading. Since polylysine can be uniformly dispersed in water or solvents and is not prone to aggregation, and the design firmly anchors each molybdenum active center onto the polymer chain, there is no opportunity for migration or aggregation. This inhibits the migration, aggregation, and sintering of active components under high temperature or long-term reaction conditions. Theoretically, one molybdenum unit corresponds to one amino acid unit, resulting in a high loading capacity, numerous catalytic sites, and high catalytic efficiency.

[0018] The N and O atoms of the Schiff base ligand form a stable six-coordinate chelate structure with Mo, which not only avoids the aggregation and deactivation of the Mo center, but also regulates the redox potential of Mo through the electronic effect of the ligand, precisely controlling the electronic structure and redox performance of the molybdenum center, making it a highly efficient redox catalytic active site, which can significantly improve catalytic selectivity and activity. Molybdenum, as the active component, replaces noble metal catalysts, significantly reducing catalyst costs. Furthermore, polylysine is a natural, biodegradable biopolymer with good water solubility and biocompatibility. The entire process uses green solvents such as water and ethanol, and uncoordinated products are removed by Soxhlet extraction, further enhancing the catalyst's environmental friendliness and long-term industrial stability. This fills the gap in using bio-based polylysine as a support for Schiff base molybdenum complexes, while also responding to the development needs of green catalysis and the circular economy. In summary, the catalyst presented in this invention combines advantages such as high loading capacity, high dispersibility, high active site utilization, resistance to sintering, inhibition of migration and aggregation, and low cost and greenness.

[0019] The catalyst prepared by this invention uses bio-based polylysine as a support and loads a salicylaldehyde Schiff base molybdenum complex through a mild and non-toxic green process. The resulting catalyst can be efficiently recovered and reused through simple filtration or centrifugation, and can maintain high catalytic activity and selectivity even after multiple cycles, effectively solving the industry pain points of traditional catalysts being difficult to recover and have poor reusability. At the same time, the good water dispersibility and rich functional groups of polylysine endow the support with excellent anti-agglomeration properties and anchoring stability. Together with the low-cost molybdenum active center, it constructs a green support-high-efficiency active center-recyclable three-in-one catalytic system, which not only reduces catalytic costs but also improves the economics and sustainability of the process. Moreover, the preparation process is simple, easy to scale up, meets the requirements of green chemistry, and has important academic value, industrial application potential, and environmental benefits, providing solid support for promoting the industrial popularization and technological upgrading of bio-based supported catalysts. Attached Figure Description

[0020] Figure 1 The infrared spectra of polylysine, salicylaldehyde Schiff base ligand, and polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst in Example 1 of this invention are shown.

[0021] Figure 2 The 3-amino-1-phenyl-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 5 of this invention 1 H NMR spectrum.

[0022] Figure 3 The 3-amino-1-phenyl-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 5 of this invention 13 C NMR spectrum.

[0023] Figure 4 The 3-amino-1-(4-bromophenyl)-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 6 of this invention 1 HNMR image.

[0024] Figure 5 The 3-amino-1-(4-bromophenyl)-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 6 of this invention 13 CNMR image.

[0025] Figure 6 The 3-amino-1-(4-isopropylphenyl)-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 7 of this invention 1 H NMR spectrum.

[0026] Figure 7 The 3-amino-1-(4-isopropylphenyl)-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 7 of this invention 13 C NMR spectrum.

[0027] Figure 8 The 3-amino-1-(pyridin-3-yl)-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 8 of this invention 1 H NMR spectrum.

[0028] Figure 9 The 3-amino-1-(pyridin-3-yl)-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 8 of this invention 13 C NMR spectrum.

[0029] Figure 10 The surface elemental composition and chemical state of the polylysine-loaded salicylaldehyde Schiff base molybdenum complex prepared in Example 1 of this invention were characterized by X-ray photoelectron spectroscopy, where (a) is the XPS full spectrum scan; (b) is the carbon 1s high-resolution spectrum; (c) is the oxygen 1s high-resolution spectrum; (d) is the nitrogen 1s high-resolution spectrum; and (e) is the molybdenum 3d high-resolution spectrum.

[0030] Figure 11 The table shows the XPS elemental analysis results of the polylysine-supported salicylaldehyde Schiff base molybdenum complex prepared in Example 1 of this invention.

[0031] Figure 12 The following are the EDS elemental analysis results of the polylysine-supported Schiff base molybdenum complex prepared in Example 1 of this invention.

[0032] Figure 13 Scanning electron microscope image of the polylysine-loaded Schiff base molybdenum complex prepared in Example 1 of this invention.

[0033] Figure 14 The bar chart shows the yield of 2-amino-3-cyanobenzopyran compounds prepared by recycling the catalyst of Example 1 of this invention 1 to 8 times.

[0034] Figure 15 The X-ray diffraction (XRD) patterns of the polylysine, salicylaldehyde Schiff base ligand, and polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst prepared in Example 1 of this invention are shown. Detailed Implementation

[0035] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. Unless otherwise specified, the experimental methods described in the embodiments of the present invention are conventional methods.

[0036] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in Examples 1 to 3, preferred embodiments are described to avoid redundancy. However, this invention is not limited to these, but can be implemented in other ways within the scope of the technical solutions defined in the appended claims. All raw materials, reagents, instruments, and equipment used in the following embodiments of this invention can be purchased commercially or prepared using existing methods.

[0037] The following detailed description, in conjunction with embodiments of the present invention and accompanying drawings, provides a clear and complete illustration of the technical solutions in these embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0038] The following are specific examples of the preparation method for polylysine-supported salicylaldehyde Schiff base molybdenum complex catalysts.

[0039] Example 1 A method for preparing a polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst includes the following steps: 1.82 g (10 mmol) of polylysine hydrochloride was dissolved in 20 mL of aqueous solution containing 0.56 g (10 mmol) of KOH. 3.66 g (30 mmol) of salicylaldehyde was added dropwise. The mixture was reacted at 50 °C for 12 h to form a yellow precipitate. After cooling to room temperature, the precipitate was filtered and washed with water and ethanol, respectively. The precipitate was then dried to obtain a yellow powder. The yellow powder was placed in a Soxhlet extractor and extracted with ethanol for 12 h to remove unreacted salicylaldehyde. The extract was then dried and placed in a vacuum drying oven at a temperature below 50 °C for 12 h to obtain salicylaldehyde Schiff base ligand (PL-SB).

[0040] 1.50 g of salicylaldehyde Schiff base ligand was dispersed in 20 mL of ethanol to obtain an ethanol dispersion of salicylaldehyde Schiff base ligand with a concentration of 75 g / L. 10 g of molybdenum acetylacetonate was dissolved in 100 mL of ethanol to obtain an ethanol solution of molybdenum acetylacetonate. The ethanol solution containing 10 g of molybdenum acetylacetonate was added dropwise to the ethanol dispersion of salicylaldehyde Schiff base ligand. The mixture was stirred at 50 °C for 12 h to obtain a yellow solution. The yellow solution was filtered to obtain the salicylaldehyde Schiff base molybdenum complex (PL-SB-Mo). The salicylaldehyde Schiff base molybdenum complex was then extracted with ethanol in a Soxhlet extractor for 12 h. The extract was removed, air-dried, and then vacuum-dried in a vacuum drying oven below 50 °C for 12 h to obtain 1.61 g of poly-L-lysine-supported salicylaldehyde Schiff base molybdenum complex catalyst. The reaction route is as follows: Example 2 A method for preparing a polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst includes the following steps: 1.82 g (10 mmol) of polylysine hydrochloride was dissolved in 100 mL of aqueous solution containing 5.6 g (100 mmol) of KOH. 12.2 g (100 mmol) of salicylaldehyde was added dropwise. The mixture was reacted at 80 °C for 1 h to form a yellow precipitate. After cooling to room temperature, the precipitate was filtered and washed with water and ethanol, respectively. The precipitate was then dried under vacuum to obtain a yellow powder. The yellow powder was placed in a Soxhlet extractor and extracted with ethanol for 12 h to remove unreacted salicylaldehyde. The extract was then dried and placed in a vacuum drying oven at a temperature below 50 °C for 12 h to obtain salicylaldehyde Schiff base ligand (PL-SB).

[0041] 1.5 g of salicylaldehyde Schiff base ligand was dispersed in 10 mL of ethanol to obtain an ethanol dispersion of salicylaldehyde Schiff base ligand with a concentration of 150 g / L. 20 g of molybdenum acetylacetonate was dissolved in 100 mL of ethanol to obtain an ethanol solution of molybdenum acetylacetonate. The ethanol solution containing 20 g of molybdenum acetylacetonate was added dropwise to the ethanol dispersion of salicylaldehyde Schiff base ligand. After stirring at 25 °C for 10 h, a yellow solution was obtained. The yellow solution was filtered to obtain the salicylaldehyde Schiff base molybdenum complex (PL-SB-Mo). The salicylaldehyde Schiff base molybdenum complex was placed in a Soxhlet extractor and extracted with ethanol for 12 h. After drying, it was placed in a vacuum drying oven below 50 °C for 12 h to obtain 1.53 g of poly-L-lysine-supported salicylaldehyde Schiff base molybdenum complex catalyst. The reaction route is as follows: Example 3 A method for preparing a polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst includes the following steps: 1.82 g (10 mmol) of polylysine hydrochloride was dissolved in 500 mL of aqueous solution containing 2.8 g (50 mmol) of KOH. 6.1 g (50 mmol) of salicylaldehyde was added dropwise. The mixture was reacted at 20 °C for 10 h to form a yellow precipitate. After cooling to room temperature, the precipitate was filtered and washed with water and ethanol, respectively. The precipitate was then dried to obtain a yellow powder. The yellow powder was placed in a Soxhlet extractor and extracted with ethanol for 12 h to remove unreacted salicylaldehyde. The extract was then dried and placed in a vacuum drying oven at 50 °C or below for 12 h to obtain salicylaldehyde Schiff base ligand (PL-SB).

[0042] 1.5 g of salicylaldehyde Schiff base ligand was dispersed in 30 mL of ethanol to obtain a 50 g / L salicylaldehyde Schiff base ligand ethanol dispersion. 5 g of molybdenum acetylacetonate was dissolved in 100 mL of ethanol to obtain an ethanol solution of molybdenum acetylacetonate. This ethanol solution containing 5 g of molybdenum acetylacetonate was added dropwise to the salicylaldehyde Schiff base ligand ethanol dispersion. The mixture was stirred at 80 °C for 12 h to obtain a yellow solution. The yellow solution was filtered to obtain the salicylaldehyde Schiff base molybdenum complex (PL-SB-Mo). The salicylaldehyde Schiff base molybdenum complex was extracted with ethanol in a Soxhlet extractor for 12 h, dried, and then vacuum dried in a vacuum drying oven below 50 °C for 12 h to obtain 1.64 g of poly-L-lysine-supported salicylaldehyde Schiff base molybdenum complex catalyst. The reaction route is as follows: Examples 1 to 3 above all successfully prepared polylysine-supported salicylaldehyde Schiff base molybdenum complex catalysts. The polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst prepared in Example 1 was selected for efficacy verification.

[0043] Experimental verification (a) Structural confirmation Figure 1 The infrared spectrum of the polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst prepared in Example 1. Figure 1 As can be seen from the infrared spectrum, poly-L-lysine (PL) is present at 3300 cm⁻¹. -1 The relatively broad absorption peaks on both sides are attributed to the stretching vibrations of primary amine N–H and amide N–H bonds; 2930 cm⁻¹ -1 The nearby peak is the C–H stretching vibration peak of the methylene group; 1650 cm⁻¹ -1 and 1540cm -1 The peaks at the amide I band exhibit C=O stretching vibration and amide II band exhibit N–H bending and C–N stretching vibration, respectively, which are typical structural features of polylysine.

[0044] After modification with salicylaldehyde to obtain the Schiff base product (PL-SB), 3300 cm -1 The characteristic peak of the amino group was significantly weakened, indicating that the primary amino group participated in the condensation reaction; at 1620 cm⁻¹ -1 The presence of a distinct –CH=N– stretching vibration peak nearby confirms the successful formation of the Schiff base structure. Simultaneously, at 1580 cm⁻¹... -1 1500cm -1 1450cmcm -1 A C=C stretching vibration peak appears at 1270 cm⁻¹. -1 The peak at this location represents the C–O stretching vibration of the phenolic hydroxyl group, further demonstrating that the salicylaldehyde structure was successfully introduced.

[0045] After coordination with molybdenum ions (PL-SB-Mo), the characteristic peak of the original Schiff base –CH=N– changes from 1620 cm⁻¹. -1 Displaced to 1590cm -1 The left and right positions indicate that the imine nitrogen atom participates in coordination; 3400cm -1 The absorption peak of the phenolic hydroxyl group was significantly weakened, indicating that the oxygen in the phenolic hydroxyl group also participated in coordination. (898 cm⁻¹) -1 and 939cm -1 The strong absorption peak at 600 cm⁻¹ is attributed to the asymmetric and symmetric stretching vibrations of Mo=O, clearly indicating that the molybdenum dioxane (VI) unit has successfully coordinated with the Schiff base ligand. Furthermore, at 600 cm⁻¹... -1 ~400cm -1 The appearance of new absorption peaks in the range is attributed to the stretching vibrations of the Mo–O and Mo–N coordination bonds, directly proving the successful preparation of the polylysine salicylaldehyde Schiff base molybdenum complex.

[0046] Figure 10X-ray photoelectron spectroscopy was used to characterize the surface elemental composition and chemical state of the poly-lysine-supported salicylaldehyde Schiff base molybdenum complex. The full spectrum showed that the sample contained only C, O, N, and Mo elements, with no impurities introduced. The C1s spectrum was fitted with four sub-peaks: CC / CH (284.8 eV), CN / C=N (286.0 eV), CO (286.5 eV), and amide C=O (288.2 eV), verifying the complete structure of the organic ligand. The Mo 3d spectrum showed characteristic double peaks of Mo(VI) (3d5 / 2: 232.5 eV, 3d3 / 2: 235.6 eV), proving that Mo is in a +6 valence coordination state, corresponding to the molybdenum dioxane center structure. The N1s spectrum was fitted with two sub-peaks: amino group (399.7 eV) and Schiff base imine bond (400.2 eV). The O1s spectrum was fitted with three sub-peaks: Mo=O (531.0 eV), CO / C=O (531.8 eV), and adsorbed water (532.3 eV). Together, these sub-peaks confirmed the formation of Mo-N and Mo-O coordination bonds, proving that the target complex was successfully synthesized.

[0047] Figure 11 XPS elemental analysis table for polylysine-supported salicylaldehyde Schiff base molybdenum complex, by... Figure 11 The characteristic double peaks (232.5 eV / 235.6 eV) in the stable coordination Mo3d spectrum of the Mo(VI) active center confirm that Mo exists in a +6 coordination state, rather than as free MoO3. The N and O atoms of the Schiff base ligand form a stable six-coordinate chelate structure with Mo, which not only avoids the aggregation and deactivation of the Mo center, but also ensures no significant catalyst loss after repeated heating reactions and recycling. Furthermore, the electronic effect of the ligand modulates the redox potential of Mo, making it a highly efficient redox catalytic active site.

[0048] The electron transfer and synergistic catalytic effect of the ligands are demonstrated by the characteristic peak (400.2 eV) of the imine bond (-CH=N-) in the N1s spectrum, indicating a strong coordination between the Schiff base ligand and the Mo center. The conjugated structure of the ligands can act as an electron channel, facilitating rapid electron transfer from the ligand to the Mo center during catalysis, thus accelerating the redox reaction. Simultaneously, the amino group of the poly-L-lysine backbone can provide protons, synergistically completing the catalytic cycle with the Mo center.

[0049] The presence of the characteristic peak (531.0 eV) of Mo=O in the O1s spectrum confirms the terminal Mo=O double bond structure at the molybdenum dioxane center. This bond is the core catalytically active site of the complex: in oxidation reactions, Mo=O can act as an oxygen donor, directly participating in the oxidation process of the substrate; in photocatalytic reactions, the Mo=O bond can act as a separation site for photogenerated carriers, inhibiting electron-hole recombination and improving catalytic efficiency.

[0050] XPS results showed that the complex surface contained only four elements: C, N, O, and Mo. Its chemical state and peak positions were consistent with the polylysine-salicylaldehyde Schiff base dioxomolybdenum structure. No characteristic signals of acetylacetone ligand or ethanol coordination were detected. Based on the characteristic binding energies of Mo3d XPS (232.5 eV, 235.6 eV) and the bimodal distance (3.1 eV), it can be determined that molybdenum in the complex is in the +6 valence (Mo VI), and is dioxomolybdenum (MoO2). 2+ The active center exists. Combining the coordination chemistry of Mo(VI) with the coordination sites of polylysine-salicylaldehyde Schiff base ligands, the molybdenum center adopts a 6-coordinate twisted octahedral configuration, indicating that the product structure is pure and the coordination environment consists only of the Schiff base, amino and phenolic hydroxyl groups and the Mo(VI) center.

[0051] Semi-quantitative analysis of the elemental composition of the poly-lysine Schiff base dioxomolybdenum complex was performed using X-ray photoelectron spectroscopy. The results showed that the atomic percentages of C, Mo, N, and O in the sample were 58.65 at.%, 2.38 at.%, 18.03 at.%, and 20.94 at.%, respectively. After molar mass conversion, the mass fractions of each element were C 46.33 wt.%, Mo 15.02 wt.%, N 16.61 wt.%, and O 22.04 wt.%, as shown in Table 1. This indicates that each gram of the complex contains 0.150 g of molybdenum, or 1.563 mmol, consistent with the theoretical elemental composition of the target material. This provides data support for subsequent quantitative analysis of catalytic performance and structure-activity relationship studies. The characteristic peak of Mo3d is located at 232.12 eV, corresponding to Mo... 6+ The oxidation state of the molybdenum Schiff base complex was confirmed to be successfully immobilized on the polylysine support. The peak positions of N1s (399.13 eV) and O1s (531.12 eV) indicate that the amino group of the support and the oxygen atom of the ligand participated in the coordination of the Mo center. The sharp peak shape and narrow half-maximum width of Mo3d indicate that the active center is well dispersed and there is no obvious agglomeration, which provides a stable active site environment for the catalytic reaction.

[0052] Table 1. Mass fraction of each element in polylysine-supported Schiff base molybdenum complex. Figure 12EDS elemental analysis of the poly-L-lysine-supported Schiff base molybdenum complex showed that the mass fractions of C, N, O, and Mo in the material were 52.20%, 13.55%, 23.49%, and 10.75%, respectively, with atomic fractions of 63.04%, 14.04%, 21.30%, and 1.63%, respectively. This elemental composition is consistent with the theoretical composition of the target material, and the detection of Mo confirms the successful loading of the Schiff base molybdenum complex onto the poly-L-lysine support. Combined with XPS analysis, the surface atomic percentage of Mo was slightly higher than the bulk atomic percentage, indicating that the active component was enriched on the material surface, which is beneficial for the full exposure of active sites in the catalytic reaction. The EDS elemental analysis results of the poly-L-lysine-supported Schiff base molybdenum complex are shown in Table 2.

[0053] Table 2. EDS elemental analysis results of poly-L-lysine-supported Schiff base molybdenum complexes Figure 13 Scanning electron microscopy (SEM) images (20,000x magnification) of the Schiff base molybdenum complex supported on poly-L-lysine show that the material exhibits a typical three-dimensional interconnected hierarchical porous network structure. This structure contains macropores of 300 nm–400 nm and mesopores of 50 nm–200 nm, consistent with the characteristic morphology of poly-L-lysine-based materials prepared by freeze-drying or phase separation methods. Compared to pure poly-L-lysine support, the surface roughness of the pore walls of the loaded material is significantly increased, with the appearance of fine protrusions and secondary micropores, providing direct morphological evidence of the successful immobilization of the Schiff base molybdenum complex. No obvious molybdenum group aggregates were observed in the images, indicating that the active centers are well dispersed on the support, which is beneficial for the full exposure of active sites and mass transfer of reactants in the catalytic reaction.

[0054] Figure 15The X-ray diffraction (XRD) patterns of polylysine, salicylaldehyde Schiff base ligand, and polylysine-supported salicylaldehyde Schiff base molybdenum complex catalysts are shown. All three samples exhibit only broadened and diffuse amorphous peaks, without sharp crystalline phase diffraction characteristic peaks, proving that all three materials have amorphous structures and no residual crystalline raw material impurities. Compared to pure polylysine (PL), PL-SB, obtained by grafting salicylaldehyde, showed a significant increase in dispersion diffraction intensity at 2θ≈21°. This is attributed to the introduction of benzene ring conjugated groups into the Schiff base structure, which enhances intermolecular π-π stacking and hydrogen bonding, thereby increasing the orderliness of molecular chain stacking. After PL-SB-Mo was obtained by coordination modification with molybdenum acetylacetone, its dispersion diffraction intensity was between that of PL and PL-SB. The coordination of metal ions disrupted some of the intermolecular conjugated stacking of ligand molecules, but the metal coordination crosslinking still resulted in a higher degree of molecular aggregation than that of unmodified polylysine. The 2θ positions corresponding to the dispersion peaks of the three samples were basically consistent, indicating that the modification and metal coordination processes only regulated the weak intermolecular interactions, and the polylysine backbone stacking framework was not destroyed. The controllable construction of Schiff base ligands and metal coordination complexes based on the polylysine backbone was successfully achieved. After loading the molybdenum complex, no sharp diffraction characteristic peaks of Mo-based crystals (MoO3, molybdenum acetylacetonate, etc.) appeared in the spectrum, proving that the molybdenum active component exists in a highly dispersed state and does not form large-sized crystal particles. This is consistent with the SEM and XPS characterization results, further indicating that the catalyst has achieved uniform dispersion of the active component and effectively inhibited the agglomeration of the active phase.

[0055] 2-Amino-3-cyanobenzopyran compounds were synthesized using the polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst prepared in Example 1 above. Specific examples of the preparation method for 2-amino-3-cyanobenzopyran compounds are given below.

[0056] Example 4 A method for preparing a 2-amino-3-cyanobenzopyran compound is as follows: Using 63.9 mg (0.1 mmol molybdenum) of poly-lysine-supported Schiff base molybdenum complex as a catalyst, 10 mmol of 10 mmol of β-naphthol, 10 mmol of benzaldehyde, and 10 mmol of malononitrile were reacted in a mixed solution of 2 mL of water and ethanol (water to ethanol volume ratio of 2:1) at 80 °C for 2 h. The mixture was filtered while hot, washed with ethanol, and the filtrate was cooled to crystallize. The crystals were then filtered and washed to obtain 3-amino-1-phenyl-1H-benzo[f]chromene-2-carboxynitrile with a yield of 91%. The filter residue was dried and could be used for the next catalytic cycle.

[0057] Example 5 A method for preparing a 2-amino-3-cyanobenzopyran compound is as follows: Using 63.9 mg (0.1 mmol molybdenum) of polylysine-supported Schiff base molybdenum complex as a catalyst, 10 mmol of β-naphthol, 10 mmol of 4-bromobenzaldehyde, and 10 mmol of malononitrile were reacted in a mixed solution of 2 mL of water and ethanol (water to ethanol volume ratio of 2:1) at 80 °C for 1 h. The mixture was filtered while hot, washed with ethanol, and the filtrate was cooled to crystallize. The crystals were then filtered and washed to obtain 3-amino-1-(4-bromophenyl)-1H-benzo[f]chromene-2-carboxynitrile with a yield of 92%. The filter residue was dried and could be used for the next catalytic cycle.

[0058] Example 6 A method for preparing a 2-amino-3-cyanobenzopyran compound is as follows: Using 63.9 mg (0.1 mmol molybdenum) of poly-L-lysine-supported Schiff base molybdenum complex as a catalyst, 10 mmol of β-naphthol, 10 mmol of 4-isopropylbenzaldehyde, and 10 mmol of malononitrile were reacted in a mixed solution of 2 mL of water and ethanol (water to ethanol volume ratio of 2:1) at 80 °C for 0.5 h. The mixture was filtered while hot, washed with ethanol, and the filtrate was cooled to crystallize. The crystals were then filtered and washed to obtain 3-amino-1-(4-isopropylphenyl)-1H-benzo[f]chromene-2-carboxynitrile with a yield of 84%. The filter residue was dried and could be used for the next catalytic cycle.

[0059] Example 7 A method for preparing a 2-amino-3-cyanobenzopyran compound is as follows: Using 63.9 mg (0.1 mmol molybdenum) polylysine-supported Schiff base molybdenum complex as a catalyst, 10 mmol of β-naphthol, 10 mmol of 3-pyridinecarboxaldehyde, and 10 mmol of malononitrile were reacted in a mixed solution of 2 mL of water and ethanol (water to ethanol volume ratio of 2:1) at 80 °C for 1.5 h. The mixture was filtered while hot, washed with ethanol, and the filtrate was cooled to crystallize. The crystals were then filtered and washed to obtain 3-amino-1-(pyridin-3-yl)-1H-benzo[f]chromene-2-carboxynitrile with a yield of 82%. The filter residue was dried and could be used for the next catalytic cycle.

[0060] Example 8 A method for preparing a 2-amino-3-cyanobenzopyran compound is as follows: Using 63.9 mg (0.1 mmol molybdenum) of poly-lysine-supported Schiff base molybdenum complex as a catalyst, 10 mmol of α-naphthol, 10 mmol of benzaldehyde, and 10 mmol of malononitrile were reacted in a mixed solution of 2 mL of water and ethanol (water to ethanol volume ratio of 2:1) at 80 °C for 1.5 h. The mixture was filtered while hot, washed with ethanol, and the filtrate was cooled to crystallize. The crystals were then filtered and washed to obtain 2-amino-4-phenyl-4H-benzo[h]chromene-3-carboxynitrile with a yield of 83%. The filter residue was dried and could be used for the next catalytic cycle.

[0061] Comparative Example 1 Using molybdenum acetylacetonate as a catalyst, the catalytic process was the same as in Example 4, with a yield of 92%.

[0062] Comparative Example 2 Using polylysine hydrochloride as a catalyst, the catalytic process was the same as in Example 4. Using 63.9 mg of polylysine hydrochloride as a catalyst, 10 mmol of β-naphthol, 10 mmol of benzaldehyde, and 10 mmol of malononitrile were reacted in a mixed solution of 2 mL of water and ethanol at 80 °C for 0.5 h to 2 h. The mixture was filtered while hot, washed with ethanol, and the filtrate was cooled to crystallize. The crystals were then filtered and washed to obtain 2-amino-3-cyanobenzopyran compounds, with a yield of 11%.

[0063] Comparative Example 3 Using a small-molecule Schiff base molybdenum complex catalyst as the catalyst, the catalytic process was the same as in Example 4. Using 33.9 mg (0.1 mmol) of the Schiff base molybdenum complex (as shown in the figure below) as the catalyst, 10 mmol of β-naphthol, 10 mmol of benzaldehyde, and 10 mmol of malononitrile were reacted in a mixed solution of 2 mL of water and ethanol at 80 °C for 0.5 h to 2 h. The filtrate was cooled and crystallized, filtered, and washed to obtain 2-amino-3-cyanobenzopyran compound with a yield of 93%. This is because the small-molecule Schiff base molybdenum complex catalyst is readily soluble in the reaction system, uniformly dispersed, and fully contacts the reactants, generally resulting in high yields and fast reactions. However, such homogeneous catalysts are difficult to recover and reuse.

[0064] Comparative Example 4 The difference between Comparative Example 4 and Example 4 is that no catalyst is used.

[0065] A method for preparing a 2-amino-3-cyanobenzopyran compound is as follows: 10 mmol of β-naphthol, 10 mmol of benzaldehyde and 10 mmol of malononitrile were reacted in a mixed solution of 2 mL of water and ethanol at 80 °C for 0.5 h to 2 h. The filtrate was cooled and crystallized, filtered, and washed to obtain 2-amino-3-cyanobenzopyran compounds with a yield of 4%.

[0066] Experimental verification The 2-amino-3-cyanobenzopyran compounds prepared in Examples 4 to 8 above were respectively subjected to... 1 HNMR and 13 C NMR detection.

[0067] Figure 2 The 3-amino-1-phenyl-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 4 1 H NMR spectrum, from Figure 2 It can be seen that, 1 H NMR (500MHz, DMSO-d6) δ7.93 (t, J=10.3Hz, 2H), 7.84 (d, J=7.9Hz, 1H), 7.43 (q, J=7.0Hz, 2H) , 7.34 (d, J=8.9Hz, 1H), 7.26 (t, J=7.3Hz, 2H), 7.21-7.11 (m, 3H), 6.97 (s, 2H), 5.30 (s, 1H).

[0068] Figure 3 The 3-amino-1-phenyl-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 4 13 C NMR spectrum, by Figure 3 It can be seen that, 13 C NMR (126MHz, DMSO) δ160.16, 147.30, 146.19, 131.29, 130.63, 129.97, 129.17, 128. 94, 127.54, 127.46, 127.07, 125.40, 124.10, 120.96, 117.26, 116.15, 58.35, 38.53.

[0069] The 1H NMR (¹³C NMR) and 1C NMR (¹³C NMR) spectra of 3-amino-1-phenyl-1H-benzo[f]chromene-2-carboxynitrile were determined in DMSO-d6 solvent, and the data are as follows: ¹H NMR (500 MHz, DMSO-d6) δ 7.93 (t, J = 10.3 Hz, 2H, naphthalene ring aryl hydrogen), 7.84 (d, J = 7.9 Hz, 1H, naphthalene ring aryl hydrogen), 7.43 (q, J = 7.0 Hz, 2H, benzene ring aryl hydrogen), 7.34 (d, J = 8.9 Hz, 1H, chromene parent nucleus aryl hydrogen), 7.26 (t, J = 7.3 Hz, 2H, 1-phenyl aryl hydrogen), 7.21–7.11 (m, 3H, phenyl / naphthalene ring residual aryl hydrogen), 6.97 (s, 2H, -NH2 amino proton), 5.30 (s, 1H, 1-CH, chromene ring methine); ¹³C NMR (126 MHz, DMSO-d6) δ 160.16 (chromene ring CO-linked quaternary carbon), 147.30 (amino-linked aromatic ring quaternary carbon), 146.19 (aromatic ring quaternary carbon), 131.29, 130.63, 129.97, 129.17, 128.94, 127.54, 127.46, 127.07, 125.40, 124.10, 120.96, 116.15 (aromatic ring carbon), 117.26 (-CN cyano carbon), 58.35 (1-CH, chromene ring tertiary carbon), 38.53 (solvent or impurity peak).

[0070] Figure 4 The 3-amino-1-(4-bromophenyl)-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 5 1 H NMR spectrum, from Figure 4 It can be seen that, 1 H NMR (500MHz, DMSO-d6) δ7.98-7.90(m, 2H), 7.85-7.78(m, 1H), 7.51-7.39( m, 4H), 7.34 (d, J=8.9Hz, 1H), 7.19-7.12 (m, 2H), 7.04 (s, 2H), 5.35 (s, 1H).

[0071] Figure 5 The 3-amino-1-(4-bromophenyl)-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 5 13 C NMR spectrum, by Figure 5 It can be seen that, 13C NMR (126MHz, DMSO) δ160.17, 147.27, 145.58, 132.09, 131.30, 130.51, 130.19, 129. 70, 129.00, 127.67, 125.49, 124.02, 120.79, 120.15, 117.28, 115.56, 57.79, 37.87.

[0072] Figure 6 The 3-amino-1-(4-isopropylphenyl)-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 6 1 HNMR spectrum, by Figure 6 It can be seen that, 1 H NMR (500MHz, DMSO-d6) δ7.96-7.89 (m, 2H), 7.87 (d, J=8.3Hz, 1H), 7.51-7.39 (m, 2H), 7.34 (d, J=9.0Hz, 1H), 7.15-7.08 (m , 4H), 6.97 (s, 2H), 5.25 (s, 1H), 2.78 (m, 1H), 1.12 (dd, J=6.9, 3.7Hz, 6H).

[0073] Figure 7 The 3-amino-1-(4-isopropylphenyl)-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 6 13 CNMR plot, by Figure 7 It can be seen that, 13 C NMR (126MHz, DMSO) δ160.23, 147.25, 147.02, 143.63, 131.28, 130.63, 129.83, 128.93, 127.57 , 127.32, 127.09, 125.39, 124.09, 121.09, 117.27, 116.46, 58.49, 38.12, 33.43, 24.27, 24.23.

[0074] Figure 8 The 3-amino-1-(pyridin-3-yl)-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 7 1 H NMR spectrum, from Figure 8 It can be seen that, 1H NMR (500MHz, DMSO-d6) δ8.54(d, J=2.4Hz, 1H), 8.38(d, J=4.7Hz, 1H), 7.95(dd, J=17.5, 8.3Hz, 2H), 7.84(d , J=8.1Hz, 1H), 7.46 (m, 3H), 7.36 (d, J=8.9Hz, 1H), 7.28 (dd, J=8.0, 4.7Hz, 1H), 7.10 (s, 2H), 5.44 (s, 1H).

[0075] Figure 9 The 3-amino-1-(pyridin-3-yl)-1H-benzo[f]chromene-2-carboxynitrile prepared in Example 7 13 C NMR spectrum, by Figure 9 It can be seen that, 13 C NMR (126MHz, DMSO) δ160.35, 148.68, 148.46, 147.41, 141.52, 135.00, 131.33, 130.35, 130. 32, 129.06, 127.77, 125.55, 124.51, 123.89, 120.73, 117.31, 115.10, 57.48, 35.98, 18.59.

[0076] Figure 14 A bar chart showing the yield of 2-amino-3-cyanobenzopyran compounds prepared by recycling the catalyst 1-8 times is provided. Figure 14 It can be seen that, The catalyst exhibits excellent cycling stability. Throughout eight consecutive cycles, the product yield remained above 90% without significant degradation, indicating that the active centers of the catalyst did not undergo severe deactivation, aggregation, or loss during repeated use. The yield showed a slight, controllable downward trend. In the initial cycles (Runs 1-3), the yield stabilized at approximately 94%–95%, demonstrating good initial activity. In subsequent cycles (Runs 4-8), the yield slowly decreased from approximately 93% to approximately 90.5%, but remained above 90% after eight cycles, with minimal overall degradation, falling within an acceptable range of performance fluctuations. This demonstrates the catalyst's good potential for industrial application. The consistently high yield after eight consecutive cycles proves the catalyst's good reusability, reducing production costs and meeting the requirements of green chemistry and industrial catalysis for catalyst economy and stability.

[0077] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst, characterized in that, The molybdenum source ethanol solution was added dropwise to the salicylaldehyde Schiff base ligand ethanol dispersion, stirred and heated to react, filtered to obtain the salicylaldehyde Schiff base molybdenum complex loaded on the polylysine side chain, and then the impurities were removed by Soxhlet extraction with ethanol. The salicylaldehyde Schiff base ligand was prepared by dissolving polylysine hydrochloride in an alkaline solution, adding salicylaldehyde dropwise while stirring and heating to achieve Schiff base condensation, followed by cooling, filtration and washing at room temperature, Soxhlet extraction with ethanol, and vacuum drying.

2. The polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst according to claim 1, characterized in that, The alkaline solution is a potassium hydroxide solution, and the molar ratio of polylysine hydrochloride to potassium hydroxide is 1:1 to 10; the molar ratio of polylysine hydrochloride to salicylaldehyde is 1:1 to 10; the molar concentration of the potassium hydroxide aqueous solution is 0.1 mol / L to 1 mol / L.

3. The polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst according to claim 1, characterized in that, The molybdenum source is any one of molybdenum acetylacetonate, molybdenum dichlorodioxide, sodium molybdate, or ammonium molybdate.

4. The polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst according to claim 3, characterized in that, The reaction temperature for the Schiff base condensation is 20℃~80℃, and the reaction time is 1h~12h. The molybdenum source is molybdenum acetylacetonate. The reaction temperature for the salicylaldehyde Schiff base ligand ethanol dispersion and the ethanol solution containing molybdenum acetylacetonate is 25℃~80℃, and the reaction time is 2h~12h.

5. The polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst according to claim 1, characterized in that, The mass concentration of the salicylaldehyde-Schiff base ligand ethanol dispersion is 50 g / L to 150 g / L.

6. The polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst according to claim 1, characterized in that, The molybdenum source is molybdenum acetylacetonate, and the mass ratio of salicylaldehyde Schiff base ligand to molybdenum acetylacetonate is 1.5:5~20, and the mass concentration of the molybdenum acetylacetonate ethanol solution is 50g / L~200g / L.

7. The method for preparing the poly-L-lysine-supported salicylaldehyde Schiff base molybdenum complex catalyst according to any one of claims 1 to 6, characterized in that, Includes the following steps: Polylysine hydrochloride was dissolved in an alkaline solution, and salicylaldehyde was added dropwise with stirring. The reaction was carried out by heating and Schiff base condensation. After cooling, the reaction product was filtered and washed at room temperature, and then extracted with ethanol by Soxhlet. The extract was dried under vacuum to obtain salicylaldehyde Schiff base ligand. Salicylic aldehyde Schiff base ligand was dispersed in ethanol to obtain a salicylic aldehyde Schiff base ligand ethanol dispersion. An ethanol solution containing a molybdenum source was added dropwise to the salicylic aldehyde Schiff base ligand ethanol dispersion, and the reaction was carried out under stirring and heating. After the reaction, the mixture was filtered to obtain a salicylic aldehyde Schiff base molybdenum complex supported on the side chain of polylysine. Impurities were removed by Soxhlet extraction with ethanol, and the extract was dried under vacuum to obtain the polylysine-supported salicylic aldehyde Schiff base molybdenum complex catalyst.

8. The application of the polylysine-supported salicylaldehyde Schiff base molybdenum complex catalyst according to claim 1 in the synthesis of 2-amino-3-cyanobenzopyran compounds.

9. The application according to claim 8, characterized in that, The preparation method of the 2-amino-3-cyanobenzopyran compounds is as follows: Using 63.9 mg of polylysine-supported Schiff base molybdenum complex as a catalyst, 10 mmol of naphthol, 10 mmol of aromatic aldehyde, and 10 mmol of malononitrile were reacted in a 2 mL water-ethanol mixture at 80 °C for 0.5 h to 5 h. The mixture was filtered while hot, washed with ethanol, and the filtrate was cooled to crystallize. The crystals were then filtered and washed to obtain 2-amino-3-cyanobenzopyran compounds, wherein the naphthol was α-naphthol or β-naphthol.

10. The application according to claim 9, characterized in that, The volume ratio of water to ethanol in the mixed solution of water and ethanol is 1~2:1.